Heat Stress Affects Seed Set and Grain Quality of Vietnamese Rice Cultivars during Heading and Grain Filling Period - Thuy, Tran Loc; Thach, Tran Ngoc; Xa, Tran Thi Thanh; Nha, Chau Thanh; My, Vo Thi Tra; Nguyen, Nguyen Thi Thao; v, Nguyen Thuy Kieu (Journal of Tropical Crop Science, 2021)
Environmental stress trigger a variety of rice plant response, ranging from alters seed set, grain yield and grain quality during flowering and grain filling stage. Efforts are required to improve our understanding of the impact of heat stress on rice production, which are essential strategies in rice cultivation. This article investigated the seed set, yield components and grain yield of Vietnamese rice cultivars (Indica germplasm) under high temperature environment during the flowering and grain filling stage. Six rice cultivars, including popular cultivars and new cultivars of Cuu Long Delta Rice Research Institute, and one popular extraneous cultivar with differences in maturing time, were grown in pots at high temperature (HT) and natural temperature condition as control (CT). All rice cultivars were subjected to the high temperature starting from the heading stage to the harvest maturity, applied by greenhouse effect. The greenhouse has about 25 cm window opening on 3 sides for air ventilation. The seed set rate of the heat-sensitive rice genotypes decreased significantly under HT, leading to a significant reduction in grain yield. The lowest seed set was recorded in “OM4900” (44.3%) and “OM18” (39.9%) under high temperature environment. The lower yield in all rice cultivars at an elevated temperature resulted in a dramatic decrease of filled grains and contributed to a loss of 1000-grain weight. ‘“OM892” is a potential rice cultivar for heat tolerant breeding program due to the seed set percentage was above 80% in both HT and CT conditions. High temperature during the grain filling stage resulted in a decreased amylose and increased chalkiness for all OM cultivars.